2007
DOI: 10.1159/000099307
|View full text |Cite
|
Sign up to set email alerts
|

ARIA (Allergic Rhinitis and Its Impact on Asthma) Classification of Allergic Rhinitis Severity in Clinical Practice in France

Abstract: Background: The Allergic Rhinitis and Its Impact on Asthma (ARIA) workshop proposes a classification of allergic rhinitis severity. It does not take into account impairment in quality of life and treatment should be adapted accordingly. Methods: Two cross-sectional surveys were designed:a spring survey, for which 1,321 practitioners enrolled 3,026 patients consulting for seasonal allergic rhinitis and an autumn-winter survey, for which 1,346 practitioners enrolled 3,507 patients consulting for perennial allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 21 publications
(16 reference statements)
2
101
0
3
Order By: Relevance
“…Alyasin and Amin in their clinic based study in Iran found that the most common category was "moderate/severe persistent" (58.3%) followed by "mild persistent" (34.4%) and "moderate severe intermittent" (4.2%) while "mild intermittent" category was the rarest (2.1%) [18]. Other studies also reported "moderate/severe persistent" as the most common form at the time of presentation [19,20]. It was observed in the present study, that "blockers" had significantly more sensitization than "sneezers-runners" to polyvalent house dust, house dust mites and fungi, while, "sneezers-runner" had more sensitization to pollens than "blockers".…”
Section: Discussionmentioning
confidence: 99%
“…Alyasin and Amin in their clinic based study in Iran found that the most common category was "moderate/severe persistent" (58.3%) followed by "mild persistent" (34.4%) and "moderate severe intermittent" (4.2%) while "mild intermittent" category was the rarest (2.1%) [18]. Other studies also reported "moderate/severe persistent" as the most common form at the time of presentation [19,20]. It was observed in the present study, that "blockers" had significantly more sensitization than "sneezers-runners" to polyvalent house dust, house dust mites and fungi, while, "sneezers-runner" had more sensitization to pollens than "blockers".…”
Section: Discussionmentioning
confidence: 99%
“…Measures of AR control include (i) symptom scores, (ii) patient self-administered visual analogue scales (VAS) (16,(76)(77)(78)(79)(80)(81), (iii) objective measures of nasal obstruction (such as peak nasal inspiratory flow, acoustic rhinometry and rhinomanometry) (82), (iv) a recent modification of the ARIA severity classification (83), (v) patients' reported outcomes such as quality of life (QOL) (7, 63) scores with several items (80,84) or composite symptom-medication scores (85). However, it is important to make the score for clinical use simple and responsive to change.…”
Section: Measures Of Allergic Rhinitis Controlmentioning
confidence: 99%
“…Table 2 shows the comparative effectiveness of drugs for allergic rhinitis. [4][5][6][7][8][9][10][11][12][13][14][15] A recent review of randomised controlled trials confirmed the efficacy of antihistamines in persistent allergic rhinitis. 16 Most patients will attain good control on intranasal steroids, and a large body of data shows that they are effective for all symptoms of allergic perennial rhinitis, including nasal obstruction, itching, sneezing, and watery rhinorrhoea.…”
Section: Swabs Smears and Biopsiesmentioning
confidence: 99%